Magnesium doped hydroxyapatite through mechanochemical synthesis - Sopyan, Iis (Trans Tech Publications, Switzerland, 2015)
The mechanochemical synthesis method was employed to synthesis hydroxyapatite (HA) and magnesium (Mg) doped hydroxyapatite (HA) powders. The effects of Mg2+ into the synthesized HA powder properties were investigated. Characterization of the synthesized HA (Mg-free HA) and Mg–doped HA at various concentrations (1% - 9% MgHA) were accomplished through X-ray diffraction (XRD) and Fourier transform infrared (FTIR) analyses. The nano size powder of HA and Mg-doped HA were successfully synthesized through the present method and the influenced of Mg2+ in the HA was also indicated by the different peaks intensity and the crystal sizes obtained.